The Effect of Mind Mapping Techniques on Writing Text Descriptions for Grade 7 Junior High School Students: Efek Teknik Mind Mapping Terhadap Penulisan Teks Deskripsi Siswa kelas 7 Sekolah Menengah Pertama - Edo Wartadinata; Dian Rahma Santoso (Academia Open, 2022)
Teaching subject of English is a compulsory. English as a subject in school immediately improved all four of the abilities. The four abilities are: speaking, listening, reading and writing. Nevertheless, there are still a lot of students of 7th Grade in SMPN 1 Jabon Sidoarjo, especially at 7 E Class, who cannot reach minimum passing grade (KKM) caused by some lack in English lesson, specifically in writing ability of Descriptive text. Common obstacles students are facing are for example: Students cannot create their writing concept of descriptive about people, thing, places, and animals. This study attempted to answer the following research question (1) is there any significant effect of mind mapping technique on students’ writing of descriptive text at seventh grade of SMPN 1 Jabon Sidoarjo. In carrying this research, the researcher formulated the objectives of the study as follows: To find out the effect of mind mapping technique on students’ writing of descriptive text at 7th grade of SMPN 1 Jabon Sidoarjo. Research method: The research design is pre-experimental research with quantitative approach, The population of this research were all students of 7E SMPN 1 Jabon Sidoarjo, The sample was seventh E class consisting of 32 students, The research instrument used in this research was test and the data collected through test was analyzed using T-test formula. The result showed that different of mean score of students’ writing before being taught using mind mapping technique was 57. Meanwhile, the mean score of students’ writing after being taught using mind mapping technique was 86,59. The finding showed that the mind mapping technique was effective to use in teaching writing descriptive text for it could improve students’ writing ability. This research has benefit in English Education study, especially for further research to enrich the resource